Effect of Energy Drink Consumption on Power and Velocity of Selected Sport Performance Activities. Issue 6 (June 2018) - Jacobson, Bert H.; Hester, Garrett M.; Palmer, Ty B.; Williams, Kathryn; Pope, Zachary K.; Sellers, John H.; Conchola, Eric C.; Woolsey, Conrad; Estrada, Carlos
Abstract : Abstract: Jacobson, BH, Hester, GM, Palmer, TB, Williams, K, Pope, ZK, Sellers, JH, Conchola, EC, Woolsey, C, and Estrada, C. Effect of energy drink consumption on power and velocity of selected sport performance activities. J Strength Cond Res 32(6): 1613–1618, 2018—Energy drinks (ED) comprise a multibillion dollar market focused on younger, active, and competitive individuals. Marketing includes claims of improved alertness and performance. The purpose of this study was to assess power (W) and velocity (m·s −1 ) of a simulated, isolated forehand stroke (FHS), and a countermovement vertical jump (CVJ) before and after ingestion of a commercially available energy shot (ES) or a placebo (PL). Healthy college-aged men and women ( N = 36) volunteers were randomly placed in the ES or PL. Before and 30 minutes after ingesting either the ES or PL, participants performed 3 FHSs and CVJs. Power and velocity of each performance was measured using a linear velocity transducer and the highest value for each measure was used for subsequent analysis. The ES group demonstrated a significant ( p = 0.05) increase in velocity and W for the FHS, but not for the CVJ. All measures remained unchanged in the PL group for both, the FHS and CVJ. Females demonstrated a significant increase in velocity over males in FHS, but not in CVJ. It was concluded that while the dose of stimulants in the ES was adequate to improve performance of smaller muscle groups, it may not have been sufficient to affect the larger muscle groups of the lower legs which contribute to the CVJ. While the ES used in the present study contained a caffeine dosage within the NCAA limit and did improve performance for the upper body, it must be noted that there are health risks associated with ED consumption.